2011
DOI: 10.1016/j.foodchem.2010.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Shelf-life extension of highbush blueberry using 1-methylcyclopropene stored under air and controlled atmosphere

Abstract: The definitive version is available at:La versione definitiva è disponibile alla URL: [http://www.journals.elsevier.com/food-chemistry] valentina.chiabrando@unito.it ABSTRACTThe potential of 1-Methylcyclopropene for controlling ripening in 'Lateblue' blueberry fruit was explored.After harvest, blueberry fruits were exposed in 1-MCP (0.3 and 0.6 µl l −1 ). After treatment samples were stored in air at 0°C for 35 days and in Controlled Atmosphere (3 kPa O2 + 11 kPa CO2) for 60 days. Quality parameters were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 28 publications
5
50
1
Order By: Relevance
“…The firmness in control and 0.1 μL L -1 1-MCP treated blueberries decreased during 80 days of storage. However, the firmness in 0.2 μL L -1 and 0.3 μL L -1 1-MCP treated blueberries increased then decreased during storage (Table 1), the firmness increase with the water loss after harvest was previously found by Allan-Wojtas et al (2001) and Chiabrando & Giacalone (2011). The firmness of blueberry fruit treated with 0.3 μL L -1 1-MCP was maintained at higher levels.…”
Section: Firmnessmentioning
confidence: 65%
See 1 more Smart Citation
“…The firmness in control and 0.1 μL L -1 1-MCP treated blueberries decreased during 80 days of storage. However, the firmness in 0.2 μL L -1 and 0.3 μL L -1 1-MCP treated blueberries increased then decreased during storage (Table 1), the firmness increase with the water loss after harvest was previously found by Allan-Wojtas et al (2001) and Chiabrando & Giacalone (2011). The firmness of blueberry fruit treated with 0.3 μL L -1 1-MCP was maintained at higher levels.…”
Section: Firmnessmentioning
confidence: 65%
“…1-methylcyclopropene (1-MCP) is used to maintain the postharvest quality and subsequent shelf life of blueberry (Delong et al, 2003;Chiabrando & Giacalone, 2011;Ji et al, 2014;Wang et al, 2014;Wang et al, 2015). The previously found that 1-MCP can effectively delays the drop of fruit crispness, firmness, springiness, cohesiveness, chewiness, resilience, commodity rate and inhibits fruit softening during storage, including 'Fuyu' persimmon (Argenta et al, 2009), Zizyphusjujube (Xie et al, 2009), pears (Wang et al, 2013a;Rizzolo et al, 2015), grape (Li et al, 2011b;Tian et al, 2011), tomato (Jeong, 2004;Zheng & Li, 2007), and apple (Li et al, 2013;Jia et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The data suggest that both the 1-MCP and ClO 2 treatments caused significantly greater TAA of green husk of walnut fruit in comparison with control (P<0.01, P<0.05, respectively) and 1-MCP was more effective than ClO 2 . The highest TAA detected was in fruit treated with 0.5 1-MCP+ ClO 2 on day 9.To date, researchers have found either no effect or a negative effect of 1-MCP on the postharvest phenol content of apple, blueberry, and Chinese kale (Hoang et al 2011;Chiabrando and Giacalone 2011;Sun et al 2012); however, Hassan and Mahfouz (2012) reported that 1-MCP treatment increased the total antioxidant capacity of coriander leaves. Ethylene induced the defense mechanism and increased the phenolics and lignin contents in postharvest 'Navelate' fruit (Cajuste and Lafuente 2007).…”
Section: Resultsmentioning
confidence: 98%
“…The consistent result with previous surveys on other plants, dealing with the role of 1-MCP on respiration and ethylene production has revealed in above text, but a negative effect of 1-MCP on decay of walnut fruit was observed. Pre-storage with 1-MCP reduces the respiration rate, ethylene production, improves the quality of a number of horticultural products (Watkins 2006;Luo et al 2009;Ma et al 2009;Massoloa et al 2011;Sun et al 2012) and retards decay in blueberry and jujube (Chiabrando and Giacalone 2011;Zhang et al 2012). 1-MCP was also effective in reducing incidence of scald, greasiness, and core flush in apple, but increased bitter pit of apple during storage and the shelf rot of pear (Sun et al 2003).…”
Section: Decay Indexmentioning
confidence: 99%
“…Fruits that were rapidly cooled after harvest and stored under CA (controlled atmosphere) conditions were the least affected in terms of weight loss. After six weeks of storage, the fruits lost 1.1% of their initial weight, while the (Alsmairat et al 2011) in comparison to the conventional cold room, where losses reached 6.7% (Chiabrando et al 2009,Chiabrando andGiacalone 2011). After being stored for a few days in a conventional cold room, blue-berried honeysuckle fruits and strawberries lost 2.5% of their original weight (Ochmian et al 2008, Ochmian 2007.…”
Section: Resultsmentioning
confidence: 99%